Impacts of dibutyl phthalate on biological municipal wastewater treatment in a pilot-scale A2/O-MBR system. (December 2022) - Wang, Jian; Tian, Yucheng; Wei, Jian; Yu, Huibin; Lyu, Chunjian; Song, Yonghui
Abstract: Dibutyl phthalate (DBP) is a typical contaminant in pharmaceutical wastewater with strong bio-depressive properties which potentially affects the operation of municipal wastewater treatment systems. Based on a year-round monitoring of the quality of influent and effluent of a full-scale pharmaceutical wastewater treatment plant in Northeast China, the DBP was found to be the representative pollutant and its concentration in the effluent ranged 4.28 ± 0.93 mg/L. In this study, the negative effects of DBP on a pilot-scale A 2 /O-MBR system was investigated. When the influent DBP concentration reached 8.0 mg/L, the removals of chemical oxygen demand (COD) and total nitrogen (TN) were significantly inhabited ( P < 0.01), with the effluent concentration of 54.7 ± 2.6 mg/L and 22.8 ± 3.7 mg/L, respectively. The analysis of pollutant removal characteristics of each process unit showed that DBP had the most significant effects on the removals of COD and TN in the anoxic tank. The α- and β-diversity in the system decreased significantly when the influent DBP concentration reached 8.0 mg/L. The impacts of DBP on known nitrifying bacteria, such as Nitrospira, and phosphorus accumulating organisms (PAOs), such as Cadidatus Accumulibacter, were not remarkable. Whereas, DBP negatively affected the proliferation of key denitrifying bacteria, represented by Simplicispira, Dechloromonas and Acinetobacter . This study systematically revealed the impacts of DBP on the pollutants removal performance and the bacterial community structure of the biological municipal wastewater treatment process, which would provide insights for understanding the potential impacts of residues in treated pharmaceutical wastewater on biological municipal wastewater treatment. Graphical abstract: Image 1 Highlights: Effects of DBP was investigated in pilot-scale with real wastewater. High influent DBP (6–8 mg/L) significantly affected the removal of TN and COD. DBP showed the greatest impact on the anoxic stage. DBP significantly inhibited the activity of denitrifying bacteria and GAOs.